ANALYSIS OF E-GOVERNMENT IMPLEMENTATION READINESS AND SERVICE QUALITY AT THE PEMALANG REGENCY DPMPTSP - Ade Nur Zaman; Sri Kamariyah; Zainal Fatah (International Journal of Multidisciplinary Reseach, 2025)
The successful implementation of E-Government initiatives depends on integrated readiness across technological, human, and process dimensions. This study examines the relationship between E-Government readiness and service quality at the Department of Investment and One-Stop Integrated Service (DPMPTSP) in Pemalang Regency. Although digital systems like the Electronic Licensing Service System (SPPE) are deployed, several challenges hinder optimal service quality. A significant barrier is human resource readiness; many staff members lack digital literacy and resist transformation, often relying on manual processes. Additionally, organizational processes remain fragmented, with back-office procedures not fully integrated into digital platforms, causing delays and bottlenecks that weaken efficiency. Technical issues, such as system bugs and unstable servers, further undermine reliability and user trust. The research underscores that technology alone cannot ensure effective E-Government. Success requires a holistic approach encompassing human resource development, process re-engineering, and organizational change management. Findings highlight the importance of investing in capacity building and digital literacy to align internal workflows with technological advances. Bridging these readiness gaps is essential for transforming digital investments into tangible improvements. Policymakers must focus on comprehensive strategies to foster a digital culture and streamline procedures to realize the full potential of E-Government for public service excellence.